1988
DOI: 10.1530/acta.0.1190474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a four-day nocturnal melatonin treatment on the 24 h plasma melatonin, cortisol and prolactin profiles in humans

Abstract: An oral preparation of melatonin was administered daily at 22.00 h to 6 healthy volunteers during summer on 4 consecutive days (days 1\p=n-\4).The daily dose was 8 mg of melatonin as a single. Three 24-h melatonin, cortisol and prolactin profiles were determined in plasma by radioimmunological methods: 1) before treatment (day 0); 2) the first day after the 4-day treatment had been stopped (day 5), 3) the third day after withdrawal of this treatment (day 7). For the melatonin rhythm, an advanced phase was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…The same study may have also influenced the first two investigations of the phase-shifting effects of melatonin in sighted people (Arendt et al 1985;Mallo et al 1988; for review, see Lewy and Sack 1997). Although we published a case report showing entrainment of a blind person to melatonin in the early 1990s (Sack et al 1990(Sack et al , 1991, it was not until the end of that decade that unequivocal entrainment (to 10 mg) could be demonstrated in a group of BFRs .…”
Section: Entrainment Of Blind People To Melatonin and The Melatonin Dmentioning
confidence: 68%
“…The same study may have also influenced the first two investigations of the phase-shifting effects of melatonin in sighted people (Arendt et al 1985;Mallo et al 1988; for review, see Lewy and Sack 1997). Although we published a case report showing entrainment of a blind person to melatonin in the early 1990s (Sack et al 1990(Sack et al , 1991, it was not until the end of that decade that unequivocal entrainment (to 10 mg) could be demonstrated in a group of BFRs .…”
Section: Entrainment Of Blind People To Melatonin and The Melatonin Dmentioning
confidence: 68%
“…On the basis of these results. the authors concluded that [Mallo et al, 1988;Wright et al, 1986;Waldhauser et al, 19871, thyroid releasing hormone [Paccotti et al, 19871, T3 or T4 [Wright et al, 19861, ACTH [Paccotti et al, 19871, growth hormone [Wright et al, 1986;Arendt et al, 1985;Waldhauseret al, 19871, luteinizing hormone [Lissoni et al, 1986;Arendt et al, 1985;Walhauser et al, 19871, FSH and TSH [Lissoni et al, 1986;Walhauser et al, 19871, or testosterone [Wright et al, 1986;Waldhauser et al, 19871. Despite the general lack of a demonstrated endocyine action, increased prolactin levels have been reported in pubertal, adolescent, and adult subjects following melatonin administration. Following administration of 0.1 mg/kg intravenous at 1500, prolactin production was significantly increased in pubertal [Mauri et al, 19851 and adolescent [Lissoni et al, 19861 subjects.…”
Section: Administration Of Melatonin In Psychiatric Patientsmentioning
confidence: 99%
“…The majority of early studies that investigated the physiological effects of melatonin focused on its potenttal to modulate neuroendocrine systems. It was initially thought that the variability in the observed hypnotic effects of melatonin may be related to an indirect effect on a second neuroendocrine system [Lissoni et al, 1986;Mallo et al, 1988;Mauri et al, 1985;Waldhauser et al, 1987;Wright et al, 19861. However, studies have consistently shown few, if any, endocrine sequelae when melatonin is administered over a short period (i.e., 1 4 days). The majority of studies report no effect of melatonin on plasma levels of markers of pituitary or adrenal function [Paccotti et al, 19881, including cortisol ics of endogenous melatonin production and exogenous melatonin administration.…”
Section: The Physiological Basis Of Melatonin's Hypnotic Effectmentioning
confidence: 99%
“…When several milligrams of melatonin, which produce supraphysiological plasma levels, are chronically or semichronically given per os in the late afternoon or evening, the melatonin rhythm is globally advanced, but its ampli tude remains very stable [1,2], Such data explain why melatonin is efficient in alleviating jet-lag syndrome when travelling from west to east [3,4], Recently, Lewy et al [5] described a melatonin phaseresponse curve (PRC) for the melatonin onset after oral administration of a low melatonin dose for 4 days. By this route of administration, however, the melatonin signal could display a heterogeneity from one subject to another, a consequence of the first-pass hepatic metabolism of the hormone.…”
Section: Introductionmentioning
confidence: 99%